An Analysis of Customer Satisfaction at Puspa's Warung Ubud, a Local Restaurant in an International Tourist Destination - Ningrum, Diva Surya; Naibaho, Hastuti (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Ubud as an international tourist destination has an increasingly competitive culinary industry, so customer satisfaction is an important factor for the sustainability of MSME-based culinary businesses. The objective of this research centers on evaluating how food quality, service quality, price fairness, and atmospherics determine customer satisfaction, while simultaneously verifying the moderating influence of culinary orientation on the food quality and customer satisfaction pathway at Puspa's Warung Ubud. A sample of 213 customers was accumulated via purposive sampling within a quantitative survey framework, followed by data execution through Structural Equation Modeling–Partial Least Squares (SEM-PLS). Positive and significant impacts on customer satisfaction were empirically demonstrated by all four core predictors: food quality, service quality, price fairness, and atmospherics. Among these, customer satisfaction is most heavily driven by service quality. Furthermore, the capacity of culinary orientation to strengthen the positive link between food quality and customer satisfaction was successfully validated. This moderation effect implies that heightened levels of culinary orientation among customers amplify their sensitivity toward food quality when assessing satisfaction. Ultimately, this study underscores that to elevate customer satisfaction within local stalls situated in international tourist areas, strategic focus must be directed toward service quality, food quality, price fairness, and restaurant atmosphere.